Long-Term Patient-Reported Functional Outcome of Polytraumatized Patients With Operatively Treated Pelvic Fractures. Issue 2 (February 2019) - Bott, Alasdair; Odutola, Adekoyejo; Halliday, Ruth; Acharya, Mehool R.; Ward, Anthony; Chesser, Timothy J. S.
Abstract : Objectives: To report the long-term functional outcome of a cohort of patients with operatively treated unstable pelvic fractures using validated patient-reported outcome measures. Design: Long-term observational study using prospective and retrospective data. Setting: Tertiary referral pelvic trauma center, Bristol, United Kingdom. Patients: Seventy-four polytraumatized patients with operatively treated unstable pelvic ring injuries (50 OTA/AO type B and 24 OTA/AO type C, mean Injury Severity Score 17) treated between 1994 and 2005. Intervention: Sixty-four (86%) patients were treated with internal fixation. The remaining 10 patients (14%) were treated with either combined percutaneous posterior fixation and anterior external fixation or external fixation in isolation. Main Outcome: Patient-reported functional outcome. Measurements: Short Form-36, with UK norm-based comparator scores and EQ-5D-3L. Results: Patients were between 11 and 22 years after injury (mean 15 years). We found no significant association between fracture classification and outcome score, but compared with age- and sex-matched scores for a UK population, differences were statistically significant in 3 of the 8 domains of health: physical function ( P = 0.04), bodily pain ( P = 0.001), and vitality ( P = 0.001). The level of disability remained constant for these patients compared with their patient-reported outcome measure scores reported 8 years previously. Conclusion: Patients who sustain an unstable pelvic fracture continue to have significant functional limitations compared with an uninjured population. These changes were not found to be related to age, injury pattern, genitourinary injury, or neurological injury. Functional outcome scores did not change over the 2 long-term time points. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.